Specification for ductile iron pipes and fittings (BSI, 1988)
Spheroidal-graphite cast-iron, Cast-iron, Cast-iron pipelines, Pipes, Pipe fittings, Dimensions, Hydraulic pressure, Pressure testing, Test pressure, Flanged fittings, Flanges, Marking, Designations, Hardness, Elongation, Dimensional tolerances, Tolerances (measurement), Mass, Linear density, Thickness, Surface treatment, Coatings, Finishes, Cement mortar, Linings (containers), Pipe coatings, Bitumens, Screwed fittings, Screwed flanges, Welded flanges, Pipe tees, Pipe collars, Pipe caps, Pipe plugs, Hydrants, Reducing couplings, Spigot-and-socket joints, Bend couplings, Blank flanges, Test specimens, Sampling methods, Tensile testing, Tensile strength, Mechanical testing, Non-destructive testing, Specimen preparation, Slip-on flanges, Design, Pipe connections, Pipe couplings, Size, Zinc, Surface defects, Gaskets, Type testing, Bend testing, Leak tests